Are intangibles more productive in ICT-intensive industries? Evidence from EU countries - Wen Chen; Thomas Niebel; Marianne Saam (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Using sectoral intangible investment data we confirm that intangible capital is a significant determinant of labour productivity growth. The sectoral setting further allows us to identify the differential impacts of intangible capital across industries with varying degrees of ICT intensity. Intangible capital appears to be significantly more productive in ICT-intensive sectors than in those that use little ICT. This finding remains robust across various alternative industry ICT intensity measures and aligns with the prior firm-level studies that place emphasis on the complementary role of intangible assets in ICT investment.
urn:nbn:de:bsz:180-madoc-371495
Keywords: E22; J24; O47; 330; Intangible capital; ICT; economic growth; labour productivity